2017
DOI: 10.1016/j.surg.2016.05.018
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia of the growing liver accelerates regeneration

Abstract: Background. After portal vein ligation of 1 side of the liver, the other side regenerates at a slow rate. This slow growth may be accelerated to rapid growth by adding a transection between the 2 sides, i.e., performing portal vein ligation and parenchymal transection. We found that in patients undergoing portal vein ligation and parenchymal transection, portal vein hyperflow in the regenerating liver causes a significant reduction of arterial flow due to the hepatic arterial buffer response. We postulated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 41 publications
2
56
4
2
Order By: Relevance
“…This appears to be a paradox, but it might represent a response to apoptosis in the deportalized liver. Schadde et al [25] recently described that tissue hypoxia in the FLR after ALPPS lead to a higher degree of regeneration, but this does not necessarily explain our findings in the deportalized lobe. Another possible explanation is that the biopsies collected at stage 2 were taken 7 days after baseline biopsies at stage 1.…”
Section: Discussioncontrasting
confidence: 55%
“…This appears to be a paradox, but it might represent a response to apoptosis in the deportalized liver. Schadde et al [25] recently described that tissue hypoxia in the FLR after ALPPS lead to a higher degree of regeneration, but this does not necessarily explain our findings in the deportalized lobe. Another possible explanation is that the biopsies collected at stage 2 were taken 7 days after baseline biopsies at stage 1.…”
Section: Discussioncontrasting
confidence: 55%
“…(15) demonstrated that in hepatocytes that were subjected to hypoxia and reoxygenation, HIF-1α targets the peroxisome rather than the nucleus, where it colocalizes with von Hippel-Lindau and the HIF hydroxylases. Nevertheless, in a rat model of portal ligation combined with parenchymal transection, Schadde et al (37) showed that different levels of hypoxia may play a critical role in liver regeneration through HIF-1α. In our study, rats subjected to PHx and bleeding demonstrated elevated HIF-1α both in the cytoplasm and the nuclei (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the parenchymal transection to accelerated and enhanced hypertrophy is further underlined by the observation that in‐situ split has been used as a rescue technique for patients whose liver fails to hypertrophy after portal vein occlusion . Clinical studies document that ALPPS procedure causes an immediate and steep rise of the portal pressure and flow into the liver remnant accompanied by a compensatory arterial constriction (HABR) . In experimental models, in ALPPS step I, but not in portal vein occlusion alone, the HABR was associated with hypoxia …”
Section: Introductionmentioning
confidence: 99%